The Illiberal Public Sphere: Media in Polarized Societies - Štětka, Václav; Mihelj, Sabina (Springer Nature, 2024)
This open access book provides the first systematic analysis of the role of the media in the rise of illiberalism, based on an original theoretical framework and extensive empirical research in Eastern Europe – a region that serves as a key battleground in the global advance of illiberalism. Liberal democracies across the world are facing a range of challenges, from the growing influence of illiberal leaders and parties to deepening polarization and declining trust in political elites and mainstream media. Although these developments attracted significant scholarly attention, the factors that contribute to the spreading of illiberalism remain poorly understood, and the communication perspective on illiberalism is particularly underdeveloped. Štětka and Mihelj address this gap by introducing the concept of the illiberal public sphere, identifying the key stages in its development, and explaining what makes illiberalism distinct from related phenomena such as populism. Their analysis reveals how and why the changing communication environment facilitates selective exposure to ideologically and politically homogeneous sources, fosters changes in normative assumptions that guide media trust, increases vulnerability to disinformation, and goes hand in hand with growing hostility to immigration and LGBTQ+ rights. The findings challenge widespread assumptions about digital platforms as key channels of illiberalism and suggest that their role shifts as the illiberal sphere progresses. The arguments presented in this book have important implications for future research on challenges to liberal democracy, as well as for journalists, media regulators and other professionals committed to rebuilding media trust and containing the forces of polarization.